10.1016/s1553-3212(08)70307-8 (CrossRef Listing of Deleted DOIs, 2000)
Aims and objectives To describe how healthcare professionals and parents of children with feeding problems experience their interactions. Methodological design A qualitative descriptive design was used, with the Family-Centred Care (FCC) model as the interpretive framework. Research methods Seven healthcare professionals and six parents participated in individual semi-structured interviews. Data were analysed using thematic analysis with inductive coding. Trustworthiness was addressed through collaborative analysis, audit trail, reflexivity and triangulation. Results The findings resulted in the overarching theme: 'Navigating the personal and structural effects on healthcare interactions'. Three main themes were developed from the participants' descriptions: 'Connecting through knowledge', 'Why communication matters' and 'Finding a way through the system'. The findings show that healthcare interactions are shaped by the level of personal and organizational knowledge in the surrounding environment, the quality of communication and the structure of the healthcare system. Study limitations All participants were Swedish-speaking from a specific region of Sweden, which limits the applicability of the findings to other cultural or healthcare contexts. Conclusion Healthcare interactions are complex and shaped by both personal and systemic factors that influence the experience over time as families move through the care process. Family-centred care for children with feeding problems should be a continuous goal in healthcare settings. To transition from 'doing for' to 'doing with' families, healthcare systems must prioritize multidisciplinary coordination, provide education for primary care professionals and address systemic barriers to ensure access and continuity of care. Achieving genuine family-centred care requires recognizing parents as essential partners on the healthcare team.